Estrategias recaudatorias y pago de arbitrios por los comerciantes del mercado municipal de Requena 2024 - Panduro Bardales, Jose Manuel (2025)
The objective of this research was to determine the relationship between collection strategies and the payment of taxes by the merchants of the Requena Municipal Market, year 2024. For such purposes, a methodology composed of a basic type, non-experimental design, correlational level and quantitative approach was used, as well as a sample of 80 participants, including merchants of the Requena Municipal Market and independent experts on the subjects of collection strategies and payment of taxes, which were the object of the questionnaire. The main results showed that the majority of those surveyed agreed on the importance of promoting collection strategies aimed at the merchants of the Requena Municipal Market, taking into account dimensions such as tax awareness and tax dissemination programs, as well as the need to establish collection strategies to encourage the payment of taxes by such merchants, taking into account dimensions such as the types of taxes and the establishment of mechanisms to promote collection. The main conclusion was the determination that there was a relationship between collection strategies and the payment of taxes by the merchants of the Requena Municipal Market, year 2024. This conclusion is based on the degree of correlation obtained for the general hypothesis, which was 0.926.